Intraoperative diagnosis of solitary cecal diverticulum not requiring surgery: is appendectomy indicated?. Issue 1 (December 2016) - Koshy, Renol; Abusabeib, Abdelrahman; Al-Mudares, Saif; Khairat, Mohamed; Toro, Adriana; Di Carlo, Isidoro
Abstract Aim To compare experience with solitary cecal diverticulum (SCD) with literature on the indication for appendectomy in cases of solitary cecal diverticulitis. Methods We retrospectively reviewed all cases of SCD in our institution from September 2011 to March 2013. Data on sex, age, ethnic origin, presence of pain in the right iliac fossa, duration of symptoms, diagnosis, management, intraoperative findings, histologic examination, hospital stay, complications, and follow-up were reviewed and analyzed. We compared this to related literature reported between 2000 and 2015. Results In the study period, 10 patients presented with an SCD. Male sex and Asian origin were predominant. All patients had pain in the right iliac fossa, with a duration of 2–5 days. In nine cases the diagnosis was made by clinical examination and laboratory testing. One patient who had undergone a previous appendectomy was diagnosed with SCD by computed tomography. This last patient was treated conservatively, four patients were treated with resection of the cecum "en bloc" with the last jejunal loop and appendix, and the other five patients were treated with appendectomies. Two patients had minor complications. All patients were followed up for a minimum of 12 to a maximum of 24 months. No recurrence was recorded in either the case treated conservatively or the cases treated by appendectomies. Conclusions In cases of operative but conservative treatment for SCD, appendectomy could be justified to avoid misdiagnosis in case of future episodes of solitary cecal diverticulitis.